FEMININITIES AND MASCULINITIES OF THE MAIN CHARACTER IN STEVEN KNIGHT’S MOVIE “SPENCER” (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2023)
This research about Femininities and Masculinities of the Main Character in  Steven  Knight's  Movie  ―Spencer‖. The method which is used to collect the data is observation method and it is analyzed by qualitative method based on theory of value in which the theoretical concept is taken mainly from Connell's book entitled Masculinities (2005) which explained about the masculine theory in it and the book from Mahaney Feminine Appeal (2003) which explained the theory of femininity as a whole. Apart from that, there are other books as a reference for this theory, concepts regarding femininity and masculinity, which refer to behavior, gender, personality, and characteristics. Based on the data review, it can be found that the types of femininities and masculinities found in the data source are four for femininities and four for masculinities, the femininities consist of the mother and spouse, the hetaira, the amazon, and the medial women. Furthermore, masculinities consist of hegemonic, subordination, complexity, and marginalization. The film actors who were found to have types of femininities and masculinities were: Princess Lady Diana.